THE ROLE OF ECONOMIC GROWTH IN ACHIEVING SUSTAINABLE DEVELOPMENT INVESTMENT, INFRASTRUCTURE AND TECHNOLOGICAL INNOVATION - Abdurashid Abdumalikovich Abdurakhimov (Galaxy International Interdisciplinary Research Journal, 2024)
Achieving sustainable development is one of the main priorities of modern economic policy. This article examines the role of economic growth in this process with a focus on investment, infrastructure and technological innovation. The study is based on the analysis of theoretical concepts and empirical data, showing how these elements contribute to sustainable development. The mechanisms by which investments in economic growth affect the social, environmental and economic aspects of sustainable development are discussed. The importance of infrastructure development as a key factor in ensuring the use of resources and services necessary for Sustainable Development is also considered. Particular attention is paid to the role of technological innovation in improving the efficiency of resource use, reducing the negative impact on the environment and promoting economic growth. The conclusion draws conclusions about the need for an integrated approach to the development of the economy, taking into account the relationship between investments, infrastructure and technological innovation in order to achieve sustainable development.